Distributed differential space-time coding techniques for two-way wireless relay networks - Alabed, S. J.; Pesavento, M.; Gershman, A. B. (2011 4th IEEE International Workshop on Computational Advances in Multi-Sensor Adaptive Processing, 2011)
Recently, several differential distributed space-time coding (DSTC) techniques for two way wireless relay networks (TWRNs) using the amplify and forward (AF) protocol have been proposed, which do not require channel state information (CSI) neither at the relays nor at the terminals. Although the simultaneous bidirectional AF protocol using DSTC has been shown to outperform the conventional four-phase DSTC strategy in the low to medium signal-to-noise ratio (SNR) region, there are mainly three disadvantages associated with it: i) the relay power wasted for transmitting information known at either side, ii) the difficulty to incorporate the direct link between the communicating terminals and iii) the considerable bias at high SNR. In this paper, we propose two differential three-phase DSTC strategies for TWRNs using the AF protocol. In our proposed strategies, the relays do not waste power to transmit known information and the direct link between the communicating terminals can be fully exploited. Simulations show a substantially improved performance in terms of bit error rate of the proposed strategies as compared to the existing strategies.